The Impact of Brexit on Human Mobility Between the UK and the EU After Five Years - Sirkeci, İbrahim; Karaköse, Gizem (Border Crossing, 2025)
This commentary examines the impact of Brexit on human mobility between the UK and the EU five years post-implementation. It highlights the significant decline in EU migration to the UK, attributed to the imposition of a points-based immigration system, and the corresponding rise in non-EU migration. Statistical data from the ONS reveal a dramatic shift in migration patterns, reflecting policy changes and societal adjustments. The analysis explores the economic ramifications, including labour shortages and increased costs, and the political consequences, such as the rise of far-right ideologies across Europe. It further discusses the social impacts, including increased xenophobia and altered perceptions of multiculturalism, alongside effects on educational mobility. The commentary concludes that Brexit has fundamentally reshaped human mobility, with lasting economic, political, and social implications for both the UK and the EU.